Gag Problem in Dental Treatment Assessment and Methods to Control it. - Karama MT Al - Nuaimy (University of Mosul, College of Dentistry, 2010)
Aims: To assess gag reflex as a problem in patients undergoing dental treatment and some measures used to control it in order to allow the patient to receive dental care such as taking anesthesia, fillings, extractions, impression, scaling and polishing of teeth and root canals. Materials and Methods: The sample chosen included 80 people between the ages 20 and 65 attended to dental clinics for fillings, extractions, impression, scaling and polishing and root canals during dental treatment these patients complained an exaggerated gag reflex. Results: In control group there was no significant difference between females and males regarding the age and duration of gag reflex, but significantly correlated in study group as a whole concerning the age and duration of gag reflex. Conclusions: Gag reflex is con-sidered as normal defense mechanism that prevents foreign bodies from entering the trachea, pharynx or larynx.